The Effect Of Yoga To The Anxiety On Pregnant WomSen In Facing The Childbirth In Yayasan Sekolah Emak Medan Tuntungan - Sari, Febriana; Lusiatun, Lusiatun; Adethia, Kismi A; Sianturi, Lamria J (Sari Mutiara Indonesia University Press, 2018)
Background: The World Health Organization (WHO) estimates there are 216 maternal deaths per 100,000 live births due to complications of pregnancy and childbirth in 2015. The total number of maternal deaths is estimated at 303,000 deaths worldwide. Indonesia is one of the developing countries as the highest contributor to the maternal deaths rate in the world. WHO estimates in Indonesia there are 126 maternal deaths per 100,000 live births with a total number of maternal deaths of 6400 in 2015. Some of the direct causes of AKI are caused by complications during pregnancy, maternity and postpartum. One of the causes of complications of childbirth is long labor which is also affected by the psychological condition of the mother. Maternal anxiety factors can cause labor to last longer and this can endanger the mother and fetal life (MOH, 2008). Purpose: Knowing the effect of yoga on pregnancy against childbirth. The research method was quasi-quantitative with a pretest and posttest nonequivalent control group design with a population of pregnant women in Sekolah Emak. Samples total of 28 people. The technique sample of purposive sampling. The data analysis is used t-independent test. Results: univariate analysis of the experimental group of 28 pregnant women respondents, with primigravida as many as 15 respondents (53.6%), secundigravida as many as 6 respondents (21.4%) and multigravida as many as 7 respondents (25%) and control groups from Univariate analysis said that there were 13 respondents (46.4%), secundigravida as many as 8 respondents (28.6%) and multigravida as many as 7 respondents (25%). While the Bivariate Analysis of the experimental group the average anxiety of pregnant women was 3.46 with a standard deviation, 508 and after yoga the average pregnant woman's pregnancy anxiety dropped to 2.04 with a standard deviation of 0.693. P-value value of 0.00, it can be concluded that there is an effect of yoga pregnant on the anxiety of pregnant women in the face of childbirth. Conclusion: there is the effect of yoga on the anxiety of pregnant women in facing the childbirth